Desenvolvimento de vidrado cerâmico mediante incorporação de resíduos sólidos - ARAÚJO , Railde Paula Diniz (2019)
Currently, measures are sought to minimize impacts on nature, especially with regard to solid waste disposal. Design has also been developing research related to sustainability, as well as developing new materials. This research aims to evaluate the possibility of the development of ceramic glazes incorporating solid residues (glass, rock and red mud) in commercial fluxes, analyzing the viability of these glazes to be burned at low temperatures in an electric oven. This research can enable ceramists a better mechanical resistance and better finishing, generating possibilities of improvement of ceramic pieces, aiming to contribute to social, cultural and economic aspects. The methodology was composed by the steps of enamel preparation, sintering at different temperatures, sliding button test, flexural strength, painting tests (dipping, brush and gun), electric oven firing and visual analysis. The push button test showed that the compositions with FTA (without residue) drain more, and its use is recommended at a temperature of 900 °C, including with residue, because it increases the viscosity of the glaze, however, the resistance test. The flexure showed that the FTA is more resistant at 950 °C, while the painting technique was the one with the brush that showed the best results. This research resulted in the development of seven color palettes totaling 125 glazes / enamels developed with solid residues (glass, rock and red mud), with varying colors, textures, gloss and good coverage in the electric oven at temperatures of 900 °C and 950 °C.